Characterizing change in vagal tone during the first three years of life: A systematic review and empirical examination across two longitudinal samples. (October 2021) - Wagner, Nicholas J.; Holochwost, Steven J.; Lynch, Sarah F.; Mills-Koonce, Roger; Propper, Cathi
Highlights: The ontogeny of vagal tone under conditions of homeostasis across infancy and early childhood is not well understood. A systematic review of 62 articles suggest that measures of respiratory sinus arrhythmia (RSA) increase over time and demonstrate moderate stability across infancy, toddlerhood, and preschool ages. A series of models fit to two diverse, longitudinal datasets suggest that baseline RSA is characterized by stable increases across infancy and early childhood. Analyses suggest that individual differences in resting RSA may become entrenched in early life. This study contributes to our understanding of the developmental trajectories of baseline RSA across infancy and early childhood. Abstract: Functioning of the parasympathetic nervous system (PNS), most often indexed by respiratory sinus arrhythmia (RSA), influences the volitional, cognitively-mediated forms of self-regulation across development. However, despite its clear relevance to children's self-regulation, and its utility as a transdiagnostic biomarker of emotion dysregulation and psychopathology, the ontogeny of vagal tone under conditions of homeostasis across infancy and early childhood is not well understood. The current research is comprised of two complementary studies. The first aims to address this gap by conducting a systematic review of the literature which has assessed resting RSA in the first three years of life. The second study uses data from two diverse, longitudinal datasets (n = 203 and n = 370) to model change in RSA from infancy to toddlerhood. Results from a systematic review of 62 studies meeting inclusion criteria suggest that measures of resting RSA increase over time and demonstrate moderate stability across infancy, toddlerhood, and preschool ages. Results from a series of models fit to longitudinal data in study two suggest that baseline RSA is characterized by stable increases across infancy and early childhood. Moreover, although there was equivocal evidence for individual variability in trajectories of RSA, the findings suggest that the individual differences in resting RSA may become entrenched in early life based on observed significant variance in growth model intercepts. In all, the current study contributes to our understanding of the developmental trajectories of baseline RSA across infancy and early childhood and should support future research examining links between children's parasympathetic regulation and their adjustment in early life.